2020
DOI: 10.1177/1475725720971205
|View full text |Cite
|
Sign up to set email alerts
|

Online Quizzes with Closed Questions in Formal Assessment: How Elaborate Feedback can Promote Learning

Abstract: Online-quizzes are an economic and objective method for formative assessment in universities. However, closed questions have been criticized for promoting shallow learning and resulting often in poor learning outcomes. These disadvantages can be overcome by embedding closed questions in effective instructional designs involving feedback. In the present field study, a final sample of N = 496 students completed the same online quiz, consisting of 60 true–false statements on the biological bases of psychology in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 60 publications
(175 reference statements)
0
26
0
1
Order By: Relevance
“…The studies reported in this Special Issue investigated all four types of potential moderators (indicated by an * in Figure 1). In terms of features of the retrieval task, multiple articles compared different types of feedback, including feedback versus no feedback (Pieper et al., 2021), correct-answer feedback with explanations versus correct-answer only feedback (Enders et al., 2021), and positive versus negative feedback (Jones et al., 2021). Furthermore, three studies in the current Special Issue examined characteristics of the learning context.…”
Section: Moderators Of the Testing Effect: An Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies reported in this Special Issue investigated all four types of potential moderators (indicated by an * in Figure 1). In terms of features of the retrieval task, multiple articles compared different types of feedback, including feedback versus no feedback (Pieper et al., 2021), correct-answer feedback with explanations versus correct-answer only feedback (Enders et al., 2021), and positive versus negative feedback (Jones et al., 2021). Furthermore, three studies in the current Special Issue examined characteristics of the learning context.…”
Section: Moderators Of the Testing Effect: An Overviewmentioning
confidence: 99%
“…Feedback typically contains information about one’s current task performance or level of understanding and can in turn enhance learning (Hattie & Timperley, 2007; Kluger & DeNisi, 1996; Wisniewski et al., 2020). Many of the articles in this Special Issue examined the benefits of feedback in combination with retrieval practice (den Boer et al., 2021; Enders et al., 2021; Jones et al., 2021; Pieper et al., 2021) or included feedback to enhance learning, even when it was not the main objective of the study (den Boer et al., 2021; Endres et al., 2021).…”
Section: Maximizing the Benefits Of Formative Testing: Providing Feedmentioning
confidence: 99%
See 2 more Smart Citations
“…Um lernförderliche Effekte zu erzielen, müssen Aufgaben beispielsweise den aktiven Abruf aus dem Langzeitgedächtnis fördern, zugleich aber so einfach sein, dass in den meisten Fällen auch die richtige Antwort abgerufen werden kann (Greving & Richter, 2018). Auch die Gewährung von Feedback im Zusammenhang mit formativen Tests spielt eine entscheidende Rolle (Kubik, Gaschler & Hausman, 2021), insbesondere wenn die Abrufbarkeit nicht gewährleistet ist und das Feedback mit zusätzlichen Erklärungen angereichert werden kann (Enders, Gaschler & Kubik, 2020). In diesenund anderen -Hinsichten unterscheiden sich formative Tests von schriftlichen Prüfungen, sodass beide Themen in der Diskussion klar voneinander getrennt werden sollten.…”
unclassified